2014
DOI: 10.4310/ajm.2014.v18.n2.a2
|View full text |Cite
|
Sign up to set email alerts
|

Canonical maps of surfaces defined by abelian covers

Abstract: In this paper, we classified the surfaces whose canonical maps are abelian covers over P 2 . Moveover, we give defining equations for Perssson's surface and Tan's surfaces with odd canonical degrees explicitly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
0
4
0
Order By: Relevance
“…From Proposition 1.1, it is an interesting problem to know the geometric realization of possible canonical degrees and many surfaces with canonical degree at most 16 have been constructed, see [9,15] for more references. However, the first example of a surface with maximal canonical degree 36 was constructed only recently by [19] as a suitably chosen C 2 × C 2 -Galois cover of a special fake projective plane X.…”
Section: Introductionmentioning
confidence: 99%
“…From Proposition 1.1, it is an interesting problem to know the geometric realization of possible canonical degrees and many surfaces with canonical degree at most 16 have been constructed, see [9,15] for more references. However, the first example of a surface with maximal canonical degree 36 was constructed only recently by [19] as a suitably chosen C 2 × C 2 -Galois cover of a special fake projective plane X.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the canonical map of the surface constructed by U. Persson is an abelian cover of P 2 . In [5], R. Du and Y. Gao showed that if the canonical map is an abelian cover of P 2 of degree d > 8, then d = 9 or 16.…”
Section: Introductionmentioning
confidence: 99%
“…The approach to construct these surfaces is using Z 3 2 −covers with some appropriate branch loci. Note that canonical maps defined by abelian covers of P 2 , and in particular the abelian covers with the group Z 3 2 , have been studied very explicitly by Rong Du and Yun Gao in [5].…”
Section: Introductionmentioning
confidence: 99%